2017
DOI: 10.1080/09688080.2017.1331684
|View full text |Cite
|
Sign up to set email alerts
|

Disability is not asexuality: the childbearing experiences and aspirations of women with disability in Zimbabwe

Abstract: The aim of this article is to elucidate the childbearing experiences and aspirations of women with disability in Zimbabwe. The paper draws from a qualitative narrative study conducted by researchers at the University of Cape Town, South Africa, which explored the experiences of sexuality of disabled women in Zimbabwe and which used the Biographic Narrative Interpretive Method to generate data. In part, the study revealed that disabled women often encounter a diverse range of challenges that are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 19 publications
(24 reference statements)
2
45
0
4
Order By: Relevance
“…Whilst there are growing efforts in highincome countries to address the needs, challenges and barriers to accessing SRH services and care for women with disabilities, those in low-and middleincome countries (LMICs) are more likely to be excluded. [7][8][9][10][11][12][13] Many factors contribute to this exclusion, including negative and stigmatising attitudes at multiple levels (e.g. family, health facilities, societal), inaccurate perceptions that women with disabilities are sexually inactive, and higher levels of sexual and gender-based violence (SGBV).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whilst there are growing efforts in highincome countries to address the needs, challenges and barriers to accessing SRH services and care for women with disabilities, those in low-and middleincome countries (LMICs) are more likely to be excluded. [7][8][9][10][11][12][13] Many factors contribute to this exclusion, including negative and stigmatising attitudes at multiple levels (e.g. family, health facilities, societal), inaccurate perceptions that women with disabilities are sexually inactive, and higher levels of sexual and gender-based violence (SGBV).…”
Section: Introductionmentioning
confidence: 99%
“…Published papers from LMICs have concluded that women with disabilities have limited understanding of SRH services and care and are thus less likely to access services and care due to a lack of inclusive and accessible information and communication. 8,11,13,14 Women with disabilities face numerous access barriers in accessing SRH services and care compared with the general population. [7][8][9][10][11][12][13] These barriers are interrelated and similar across different settings 15 and can be categorised broadly into those related to physical structure, transportation, finance, communication and stigmatising attitudes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations